B cell development: transcriptional regulation and immunological mechanisms in homeostasis - Gómez-Manríquez, Jorge; Hernández-Bello, Jorge; Muñoz-Valle, José Francisco; Sifuentes-Franco, Sonia; Graciano-Machuca, Omar; Morales-Núñez, José Javier (Frontiers in Immunology, 2025)
B lymphocytes are essential elements of the adaptive immune response, performing critical functions such as antigen presentation, cytokine secretion, and antibody production. Their development follows a tightly regulated progression from hematopoietic stem cells to differentiated plasma or memory cells, orchestraeted by key transcriptional factors including PU.1, Ikaros, E2A, Pax-5, and BCL6. These factors govern gene expression essential for processes such as V(D)J recombination, somatic hypermutation, and immunoglobulin class switching—ensuring proper lineage commitment and the maintenance of immunological tolerance. Dysregulation of these pathways, whether through genetic or epigenetic alterations or chronic inflammatory stimuli, can result in autoimmunity, persistent inflammation, or B cell malignancies. This review provides a comprehensive analysis of the transcriptional and immunological mechanisms underlying B cell development and homeostasis, emphasizing their roles in disease pathophysiology and potential as therapeutic targets.